Coordination of Patterning and Growth by the Morphogen DPP. - Restrepo, S.; Zartman, J.J.; Basler, K. (Current Biology, 2014)
The elegance of animal body plans derives from an intimate connection between function and form, which during organ formation is linked to patterning and growth. Yet, how patterning and growth are coordinated still remains largely a mystery. To study this question the Drosophila wing imaginal disc, an epithelial primordial organ that later forms the adult wing, has proven to be an invaluable and versatile model. Wing disc development is organized around a coordinate system provided by morphogens such as the TGF-? homolog Decapentaplegic (DPP). The function of DPP has been studied at multiple levels: ranging from the kinetics of gradient formation to the establishment and maintenance of target gene domains as well as DPP's role in growth control. Here, we focus on recent publications that both enrich our view of DPP signaling but also highlight outstanding questions of how DPP coordinates patterning and growth during development.